Identification of weed population and determination of plant performance in aerobic rice under different rates of NPK application / Wan Nur Aifa Wan Din - Wan Din, Wan Nur Aifa (Faculty of Plantation and Agrotechnology, 2019)
Rice is as a staple food that consumed daily by the people. Aerobic rice was produced through crossing technique in between the traditional upland, which is drought tolerance and improved lowland, which is high yield. Application of fertilizer in aerobic rice has been proved as one of the factors affected plant growth and development, hence, lead to produce optimum yield. However, attainment of effectiveness of nutrient supply is rely on the different rates of fertilizer application. Glasshouse study in Randomized Complete Block Design (RCBD) was conducted at Greenhouse University Technology MARA (UiTM) Jasin. This experiment was carried out to determine the influence of various NPK levels, which are 3gram, 6gram and 9gram towards weed population infestation and to evaluate the growth performance of aerobic rice (AERON 1) such as plant height, number of tiller and chlorophyll content upon different sampling dates. Leptochloa chinensis was found as predominant weed species in all treatments followed by Fimbristylis miliacea, Cleome rutidosperma, Cassia occidentallis and Ludwigia hyssopifolia. Besides that, plant heights, number of tillers and chlorophyll contents for AERON 1 were recorded highest in the treatment of 9gram NPK fertilizer.